TRANSLATIONAL CHARACTERISTICS OF THE CONCEPT OF “FRIENDSHIP” - Nazarova , Zebinisobonu Ravshanjon qizi (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
The purpose of the article is to illustrate some peculiarities of translation the concept “friendship”. As the translation is crucial part of learning and teaching a foreign language, translational characteristics is main part of the following thesis. Moreover, the thesis demonstrates new approaches and new versions of the concept “friendship”.